The use of electric fields for edible coatings and films development and production: A review - Souza, B. W. S. (2010)
Edible films and coatings can provide additional protection for food, while being a fully biodegradable, environmentally friendly packaging system. A diversity of raw materials used to produce edible coatings and films are extracted from marine and agricultural sources, including animals and plants. Electric fields processing holds advantage in producing safe, wholesome and nutritious food. Recently, the presence of a moderate electric field during the preparation of edible coatings and films was shown to influence their main properties, demonstrating its usefulness to tailor edible films and coatings for specific applications. This manuscript reviews the main aspects of the use of electric fields in the production of edible films and coatings, including the effect in their transport and mechanical properties, solubility and microstructure.